Proceedings of the 19th Annual SIGdial Meeting on Discourse and Dialogue 2018
DOI: 10.18653/v1/w18-5016
|View full text |Cite
|
Sign up to set email alerts
|

Language-Guided Adaptive Perception for Efficient Grounded Communication with Robotic Manipulators in Cluttered Environments

Abstract: The utility of collaborative manipulators for shared tasks is highly dependent on the speed and accuracy of communication between the human and the robot. The run-time of recently developed probabilistic inference models for situated symbol grounding of natural language instructions depends on the complexity of the representation of the environment in which they reason. As we move towards more complex bi-directional interactions, tasks, and environments, we need intelligent perception models that can selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Table II shows the impact of adaptive perception on the compactness of the approximated world representations. Consistent with previous evaluations [20], reducing the cardinality of the world model improves the runtime of language grounding. Figure 3 demonstrates the impact of adaptive perception for the example instruction "drive to the nearest cup in the kitchen."…”
Section: A Adaptive Perceptionsupporting
confidence: 82%
See 3 more Smart Citations
“…Table II shows the impact of adaptive perception on the compactness of the approximated world representations. Consistent with previous evaluations [20], reducing the cardinality of the world model improves the runtime of language grounding. Figure 3 demonstrates the impact of adaptive perception for the example instruction "drive to the nearest cup in the kitchen."…”
Section: A Adaptive Perceptionsupporting
confidence: 82%
“…In previous experiments [20], we observed that language grounding was faster in environments inferred by adaptive perception than non-adaptive perception. Also the adaptive perception was found to be faster than its counterpart.…”
Section: A Adaptive Perceptionmentioning
confidence: 65%
See 2 more Smart Citations
“…The approach to natural language understanding of robot instructions in this paper relies on variations of the Distributed Correspondence Graph (DCG) [3,4,10,15,17,42,45,75,79,80]. The DCG and the Hierarchical Distributed Correspondence Graph (HDCG) [22], Adaptive Distributed Correspondence Graph (ADCG) [82], and Hierarchical Adaptive Distributed Correspondence Graph (HADCG) [83] variations of the model formulate the problem of natural language understanding as probabilistic inference in a factor graph using models to approximate the conditional probabilities of a correspondence variable φ in the context of language Λ, symbols Γ, and the environment model S from corpora of annotated examples.…”
Section: Natural Language Understandingmentioning
confidence: 99%